Leucoagaricus subtropicus sp. nov. (Agaricaceae) from Anhui Province, China - Yang, Yu; Xiao, Yuan-Pin; Luo, Xia; Gong, Yin-Ping; Wang, Shuai; Yang, Meng-Meng; Tao, Ying-Ying (Phytotaxa, 2023)
Leucoagaricus subtropicus sp. nov., a new species of lepiotaceous fungi, is described from Anhui Province, China. Phylogenetic analyses based on combined sequence data from ITS and LSU indicated that it forms clusters within the Leucoagaricus. Moreover, morpho-anatomical analyses provided further confirmation of its distinctiveness. This novel taxon is mainly recognized by its medium-size, brownish-red fibrous scales in pileus with darker in the middle, greyish red to blood-red when bruised, brownish-orange droplets on base stipe, polymorphic cheilocystidia. The observed morphological and molecular phylogenetic differences clearly distinguish our species from all previously known species of Leucoagaricus, confirming its novelty. The new species is described, illustrated, and compared to species with similar characteristics.